Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/adhm.201900425
|View full text |Cite
|
Sign up to set email alerts
|

Human Neural Tissues from Neural Stem Cells Using Conductive Biogel and Printed Polymer Microelectrode Arrays for 3D Electrical Stimulation

Abstract: Electricity is important in the physiology and development of human tissues such as embryonic and fetal development, and tissue regeneration for wound healing. Accordingly, electrical stimulation (ES) is increasingly being applied to influence cell behavior and function for a biomimetic approach to in vitro cell culture and tissue engineering. Here, the application of conductive polymer (CP) poly(3,4‐ethylenedioxythiophene)‐polystyrenesulfonate (PEDOT:PSS) pillars is described, direct‐write printed in an array… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
92
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(99 citation statements)
references
References 40 publications
5
92
0
Order By: Relevance
“…Notably, early to late expression of Tuj1 by differentiating cells is consistent with Tuj1 being present in mitotically active neuronal precursors, as well as newly formed immature postmitotic neurons and more differentiated neurons [16]. Finally, initial studies of conventional electrical stimulation of the iPSCs within neural induction medium affirms published reports of augmented cell differentiation using electrical stimulation contemporaneously with cell-specific induction media [5][6][7][8].…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…Notably, early to late expression of Tuj1 by differentiating cells is consistent with Tuj1 being present in mitotically active neuronal precursors, as well as newly formed immature postmitotic neurons and more differentiated neurons [16]. Finally, initial studies of conventional electrical stimulation of the iPSCs within neural induction medium affirms published reports of augmented cell differentiation using electrical stimulation contemporaneously with cell-specific induction media [5][6][7][8].…”
Section: Discussionsupporting
confidence: 76%
“…Here, we describe the use of electrical stimulation for differentiating human iPSCs and expound the versatility of electroactive PPy:DBS. Initial CV and impedance studies critically demonstrated the conductivity and stability of PPy:DBS films necessary for iPSC stimulation, and affirm the method used for their preparation [5,13]. In addition, immunophenotyping of the iPSCs confirmed pluripotent cell state, with undifferentiated cells ubiquitously expressing pluripotency markers OCT4, SOX2, SSEA4, TRA-1-60, and TRA-1-81.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations